O Caráter verbo-nominal do aspecto em esperanto - Laroca, Maria Nazaré de Carvalho (2009)
This dissertation demonstrates that aspectual function is performed in Esperanto through grammatical discursive strategies that interact with semantic value or Aktionsart of participial and verbal forms. According to functionalist definitions we consider as presupposition the compositional character of aspect, which manifests as a property of predication. The corpora examined attest that different resources of aspectualization occur in Esperanto. This means that it corroborates our general hypothesis that grammatical aspect is present and it is functional in Esperanto language. We explicit strategies that Esperanto user utilizes to code grammatical aspect, i.e., the way the action, the event or the verbal process occurred, occur or they shall occur, focusing the duration and/or realization codified as verb or verbal name, i.e., participle.